PTH-033 Spyglass: a four year experience. (8th June 2018) - Johnston, Tom; Abeysekera, Kushala; Sinha, Ashish; Arnold, Ben; Welsh, Sarah; Portal, Jim; Strickland, Andy
Abstract : Introduction: Diagnostic and therapeutic single operator cholangioscopy (SOC) has increased in importance for stricture assessment and management of cholelithiasis. The technique is often employed under general anaesthetic but can be performed using conscious sedation. The primary aim of this study was assessment of diagnostic accuracy of histology taken for stricture assessment and stone clearance rates during SOC. Methods: A single centre retrospective analysis was performed of consecutive SOCs over 4 years at BRI (tertiary referral centre for South West England and South Wales), including fibreoptic ( Spyglass Legacy ) and high resolution digital systems ( Digital Spyglass ). Recorded parameters included sedation/general anaesthetic (GA) dosages, stone clearance, use of electrohydraulic lithotripsy (EHL), histology, complications, final diagnosis and correlation with histology. Results: Between 2013–2017, 164 patients (mean age 65.4 years (range 22–91); 79 females; 85 males) had 206 SOC procedures, referred from 12 hospitals. 15 SOCs were performed in 2013 compared to 64 in 2017. 54% of patients were referred for stricture assessments, 43% for SOC+EHL; 5 patients had assessment of an indeterminate lesion on imaging. 7 patients had SOC under GA. 97% of patients had conscious sedation: average midazolam dose was 7 mg; fentanyl 141 mcg; buscopan 24 mg. Macroscopic assessment of strictures and indeterminate lesions correlating with malignancy had a sensitivity, specificity and accuracy of 90% (95%CI 79–97), 83% ((95% CI 71–96) and 86% (78.5%–92%) respectively. Histological correlation with final diagnosis increased over the study, from 77% in 2015 to 87% in 2017. Complete stone clearance rose from 50% in 2014 to 85% by 2017. 70% of patients had complete stone clearance at 1 st attempt. 4.3% of patients developed complications post SOC. Post-ERCP pancreatitis (PEP) was the commonest adverse event (2.4%; n=5/206). Conclusions: The role of SOC in tertiary centres for identification of biliary lesions and management of difficult choledocholithiasis continues to grow. The South West service is centralised to one centre with a clear improvement in diagnostic accuracy for malignancy and stone clearance rates. Diagnostic accuracy rates mirror figures quoted in literature, most recently Japanese data in 2017. 1 2 Adverse events were lower than those widely reported, but PEP remains the commonest cause. SOC under conscious sedation is both safe and effective. References: . Kalaitzakis E, Webster GJ, Oppong KW, et al. Diagnostic and therapeutic utility of single-operator peroral cholangioscopy for indeterminate biliary lesions and bile duct stones. Eur J Gastroenterol Hepatol2012;24(6):656–664. . Ogura T, Imanishi M, Kurisu Y, et al. Prospective evaluation of digital single-operator cholangioscope for diagnostic and therapeutic procedures (with videos). Dig Endosc2017;29:782–789.